THE IMPACT OF CERTAIN PSYCHOLOGICAL FACTORS OF INVESTORS AND MANAGERS ON THE CAPITAL STRUCTURE - Babanić, Mirko (The European Journal of Applied Economics, 2018)
Psychology represents the basic requirement for the emergence ofdisciplines such as behavioral finance and behavioral economics. It hascontributed to a better understanding of the behavior of economic actorsunder conditions of risk arising from the imperfections of cognitiveabilities of human beings. Consequently, it is necessary to change theeconomic models based on mathematical laws in favor of descriptivemodels that consider the cognitive abilities of the human mind. Themost common decisions that are being studied in the field of behavioralfinance are the decisions regarding capital structure in companies.The methodology in this paper is based on the net operating incomeapproach. This approach is analyzing the financial section of incomestatement that refers to the financial expenses of the companies. Financialexpenses are assumed to be fixed, determining financial break even, asa consequence of use of financial leverage. The main task of this paperis to determine the impact of some psychological factors in the termsof capital structure and financial leverage, through two case studies ofcomparative analysis of income statements of the companies Puma andAdidas that will consequently affect the achievement of financial breakevenswell as the profitability of the companies. Therefore it is possibleto conclude that some analyzed psychological aspects in the process offinancial decision making of investors and managers can influence thecapital structure decisions, which can be a subject of further researches.